2018
DOI: 10.1111/jgs.15528
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Memory Care Clinic: Design, Implementation, and Initial Results

Abstract: The Integrated Memory Care Clinic (IMCC) is a patient-centered medical home as defined by the National Committee for Quality Assurance directed by advanced practice registered nurses (APRNs) caring for persons living with dementia (PLWD); physicians provide specialty consultation but do not direct care or care planning. The IMCC incorporates geriatric nursing, social work, and APRNs from neurology, gerontology, palliative care, and geriatric psychiatry. APRNs provide comprehensive, coordinated primary care for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…Several evaluations have suggested that such approaches have considerable potential for improving outcomes for people with dementia and their family caregivers (for example, delayed nursing home admission and reduction in caregiver distress) 541–551 . Current research is attempting to determine the feasibility of these models beyond the specialty settings in which they currently operate 552–555 . One approach to accelerate the adoption of dementia care innovations is to reform payment reimbursement strategies for providers, such as paying for services provided to caregivers and identifying metrics of success in dementia care 556 …”
Section: Caregivingmentioning
confidence: 99%
“…Several evaluations have suggested that such approaches have considerable potential for improving outcomes for people with dementia and their family caregivers (for example, delayed nursing home admission and reduction in caregiver distress) 541–551 . Current research is attempting to determine the feasibility of these models beyond the specialty settings in which they currently operate 552–555 . One approach to accelerate the adoption of dementia care innovations is to reform payment reimbursement strategies for providers, such as paying for services provided to caregivers and identifying metrics of success in dementia care 556 …”
Section: Caregivingmentioning
confidence: 99%
“…Several evaluations have suggested that such approaches have considerable potential for improving outcomes for people with dementia and their family caregivers (for example, delayed nursing home admission and reduction in caregiver distress) 499‐508 . Current research is attempting to determine the feasibility of these models beyond the specialty settings in which they currently operate 509‐512 …”
Section: Caregivingmentioning
confidence: 99%
“…[499][500][501][502][503][504][505][506][507][508] Current research is attempting to determine the feasibility of these models beyond the specialty settings in which they currently operate. [509][510][511][512] In 2016, the National Academies of Sciences, Engineering, and Medicine released Families Caring for an Aging America, a seminal report that includes a number of recommendations to refocus national health care reform efforts from models of care that center on the patient (person-centered care) to models of care that also explicitly engage and support the patient's family (family-centered care). 404 These service models recognize the important role family members play in providing care and incorporate family caregivers during the delivery of health care to their relatives with dementia.…”
Section: Enhancing Health Care For Family Caregiversmentioning
confidence: 99%
“…There are reports of experiences of successful MU in low- to middle-income patients ( 64 ) and in rural areas, using telehealth evaluations ( 23 ). Other MU have been established in primary care instead of specialized care settings ( 65 ) and can be composed mainly of nurses that can assess and manage specific symptoms ( 66 , 67 ). Some MU treat and manage different types of dementia such as frontotemporal dementia ( 68 ).…”
Section: Discussionmentioning
confidence: 99%